Integrasi Human Capital dan Digital Literacy Mahasiswa Fakultas Ekonomi UNIMED sebagai Keuntungan Investasi Pendidikan : Sebuah Studi Kualitatif: Penelitian - Dilli Salsa Fira; Febriana Krisdayanti Barus; Khairiah; Dwi Susanti; Revita Yuni (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research aims to describe how students at the Faculty of Economics, Medan State University (FE UNIMED), build human capital and integrate it with digital literacy as a form of educational investment benefit. Using a descriptive qualitative approach with interviews, observations, and documentation, the study found that mid-to-late semester students experienced increased competency thru KKNI-based tasks that required the application of theory, analysis, and collaborative work. Students' digital literacy is also developing, encompassing technical skills, information evaluation, and the ethical use of technology. The integration of both provides academic, social, and economic benefits, including increased self-confidence, internship opportunities, and digital entrepreneurship activities. This research concludes that education at FE UNIMED serves as a long-term investment that strengthens students' competitiveness in the digital economy era.